Very early social support following mild stroke is associated with emotional and behavioral outcomes three months later. (January 2017) - Villain, Marie; Sibon, Igor; Renou, Pauline; Poli, Mathilde; Swendsen, Joel
Objective: To investigate whether social contact and support received during hospitalization for acute ischemic stroke predict depression and daily life functioning three months later. Design: Prospective observational study using Ecological Momentary Assessments to evaluate the number of social contacts as well as social support received from family, friends and medical staff within 24 hours following admission for stroke. Patients also monitored depression symptoms and behavior in real-time and in daily life contexts three months later. Setting: A university hospital acute stroke unit. Subjects: Thirty-four mild ischemic stroke patients. Interventions: None. Main measures: One-day Ecological Momentary Assessments immediately following stroke collected information concerning perceived social support, number of social contacts and depression symptoms. Ecological Momentary Assessments was repeated three months later and addressed depression levels as well as activities of daily living, such as working, cooking, shopping and housework. Results: The number of social interactions received at hospitalization did not predict three-month outcomes. However, a better quality of moral support from friends and family immediately after stroke was associated with decreases in later depression levels ( p = 0.041) and increases in activities of daily living ( p = 0.011). Material support from friends and family was associated with increases in activities of daily living ( p = 0.012). No effect was observed for support received from medical staff. Conclusions: Patient perceptions of better support quality, and not quantity, immediately following mild stroke, are associated with better behavioral and emotional outcomes three months later.